1991
DOI: 10.1002/hed.2880130209
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, quantification, and potential clinical value of the epidermal growth factor receptor in head and neck squamous cell carcinomas

Abstract: Epidermal growth factor (EGF) stimulates the growth of several types of epithelial tissues and possesses a strong mitogenic activity that is mediated through its cell surface receptor (EGFR). The aim of this study was to characterize EGFR and measure its levels in head and neck tumors biopsies (70 patients); use of a simplified competition technique with a radiolabeled ligand allowed evaluation of functional EGFR. Five samples (4 tumors and 1 control) were used to characterize EGF binding. Graphic representati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
103
1
3

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(113 citation statements)
references
References 19 publications
6
103
1
3
Order By: Relevance
“…Several studies have demonstrated the over expression of EGFR in primary oral cancers and OSC cell lines (Frank et al, 1991;Satini et al, 1991;Shirasuna et al, 1991). Our results showed the over expression of EGFR in newly established YD cell lines.…”
Section: Discussionsupporting
confidence: 69%
“…Several studies have demonstrated the over expression of EGFR in primary oral cancers and OSC cell lines (Frank et al, 1991;Satini et al, 1991;Shirasuna et al, 1991). Our results showed the over expression of EGFR in newly established YD cell lines.…”
Section: Discussionsupporting
confidence: 69%
“…Over the past decade, comprehensive data have been accumulated that strongly support a role for EGFR and its ligands in tumour development and growth. This is particularly true for squamous cell carcinoma of the head and neck, where EGFR is considered to be one of the major prognostic factors (Santini et al, 1991;Dassonville et al, 1993;Salomon et al, 1995;Grandis et al, 1996Grandis et al, , 1998Maurizi et al, 1996). As a result, EGFR has become an attractive target for novel anticancer therapies, particularly in HNC.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of EGFR expression have been correlated with poor prognosis (Santini et al, 1991;Dassonville et al, 1993). EGFR signalling has been found to control not only cell growth, but also angiogenesis and DNA repair (Wheeler et al, 1999;Schlessinger, 2000), and has recently been assessed as an innovative target in cancer therapy and particularly in HNC.…”
mentioning
confidence: 99%
“…(In our unpublished data we have also included other cytokines, such as IL-4, IL-8, and 1155 IL-10, for the studies, and all of them showed no specific change). The fact that the expression of EGFR mRNA increased in the 2 to 3 weeks after EBV infection and then gradually decreased to the original level by 4 weeks after infection indicates that EBV infection activates the host cellular EGFR expression, which may result in an increase in the rate of cellular proliferation through a paracrine or autocrine pathway (Boonstra et al, 1995;Santini et al, 1991;Zheng et al, 1994).…”
Section: Identification Of Mrna Expression Of Growth Factors/cytokinementioning
confidence: 99%